2020
DOI: 10.3390/su12093879
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Influencing Factors Research of the Energy and Power Efficiency in China: Based on the Supply-Side Structural Reform Perspective

Abstract: China’s supply-side structural reforms are facing bottlenecks in the energy and power sector, and improving energy and power efficiency and advancing reforms are urgent. To promote sustainable development, based on panel data from 30 provinces and cities in China from 2009 to 2017, this paper uses the super-efficiency DEA method to measure energy and power efficiency; explores the trend of energy and power efficiency changes before and after reform; uses the Tobit model to identify key efficiency factors; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Jia et al (2021) found that doped metal oxides can play a synergistic role in enhancing the mercury removal performance of the modified biochar [18], and this shows that the development and application of related technologies and methods can help to improve efficiency. Song et al (2020) used the super-efficiency DEA method to measure China's power efficiency level from 2009 to 2017 and explored the trend of efficiency changes before and after China's supply-side reforms, indicating that the efficiency after reforms showed a fluctuating upward trend, including technological progress, economic development, and opening to the outside world, positively affecting power efficiency [19]. Although the above studies incorporate various pollution factors that affect environmental quality into the model, only one or two of them are considered, which lacks comprehensiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jia et al (2021) found that doped metal oxides can play a synergistic role in enhancing the mercury removal performance of the modified biochar [18], and this shows that the development and application of related technologies and methods can help to improve efficiency. Song et al (2020) used the super-efficiency DEA method to measure China's power efficiency level from 2009 to 2017 and explored the trend of efficiency changes before and after China's supply-side reforms, indicating that the efficiency after reforms showed a fluctuating upward trend, including technological progress, economic development, and opening to the outside world, positively affecting power efficiency [19]. Although the above studies incorporate various pollution factors that affect environmental quality into the model, only one or two of them are considered, which lacks comprehensiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The DEA method has been widely used to study energy efficiency as an efficiency assessment method [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. DEA is recognized in the literature as a powerful method, more suitable for performance measurement activities than traditional econometric methods, such as regression analysis and simple ratio analysis [8,15].…”
Section: Literature Review Using Dea and Dea-sementioning
confidence: 99%
“…Therefore, in this study, a type of data envelopment analysis (DEA) technique known as super-efficiency (SE) was used to evaluate the performance of energy research projects. The data envelopment analysis method has been widely used to study energy efficiency as an efficiency assessment method [1][2][3][4][5][6][7][8][9][10][11][12][13][14] because it offers several key advantages. When using DEA to analyze efficiency, weight values are automatically calculated in the model itself.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations